Development of Rice Bran Mixed Porous Clay Bricks for Permeable Pavements: A Sustainable LID Technique for Arid Regions - Fawaz Alharbi (Sustainability, 2021)
Permeable pavement provides sustainable solutions for urban stormwater management. In this research, the potential of rice bran mixed porous clay bricks were evaluated for permeable pavements. Physical, mechanical and hydrological properties along with stormwater treatment capabilities of the brick samples were assessed. The study found that ratio of rice bran and clay soil has significant impacts on the properties of the produced bricks. Water adsorption and porosity increased with increasing rice bran ratio. Compressive strength of brick samples decreased from 29.6 MPa to 6.9 MPa when the ratio of rice bran was increased from 0% to 20%. The permeability coefficient increased from 4 × 10−4 to 1.39 × 10−2 mm/s with the increase in rice bran from 0% to 30%. The preamble clay bricks were efficient to remove turbidity, total suspended solids (TSS), five days’ biochemical oxygen demand (BOD5), and heavy metals (Mn, Cu, and Zn) from stormwater to meet the World Health Organization (WHO) standard for wastewater reuse application. The bricks with ≤10% of rice bran achieved the American Society for Testing and Materials (ASTM) standard of the desire compressive strength and permeability coefficient for pedestrian and light traffic pavements. The porous bricks prepared in this study can be used to construct permeable pavements and would be a sustainable low impact developments technique for stormwater management in urban areas.